The role of rock mass modulus and structure on cave propagation behaviour - Sainsbury, B-A; Sainsbury, D (Caving 2026: Sixth International Conference on Block and Sublevel Caving, 2026)
Caveability is commonly assessed using strength-based approaches. However, field observations show that cave propagation often deviates from these predictions, even when sophisticated numerical predictions are completed. This paper examines the role of rock mass modulus and damage evolution in controlling cave behaviour under excavation-induced unloading stress paths. Conceptual modelling demonstrates that for identical strength parameters, variations in rock mass modulus produce order of magnitude differences in prediction of cave height, propagation rate and tonnes extracted. Stress path analysis shows that the key difference between rock mass modulus cases is therefore not the stress path itself, but how far that path progresses towards failure. In higher stiffness rock masses, damage remains distributed and propagation is constrained, whereas lower stiffness conditions promote localisation and sustained growth and progress further towards failure. Geological structure enhances cave propagation only when intersected and when the stiffness regime permits damage localisation. The results demonstrate that in some cases, cave propagation is governed by stiffness-controlled damage evolution rather than strength exceedance alone, and that rock mass modulus must be treated as a primary input parameter in caveability assessments. However, reliable estimation of modulus remains highly uncertain, as commonly used empirical relationships can produce values that differ by an order of magnitude or more for the same rock mass. This variability introduces significant uncertainty into design and reinforces the need to more routinely characterise rock mass modulus through in situ monitoring and back-analysis.
Keywords: caving; cave propagation; cave initiation; crack damage criterion; rock mass modulus; structure